2014
DOI: 10.1021/sc500444w
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Cholinium Carboxylate Ionic Liquids in PEG-Based Aqueous Biphasic Systems

Abstract: This work aims at exploring new sustainable separation processes based on ionic liquids. Aqueous biphasic systems (ABS) based on poly(ethylene glycol) (PEG) with low molecular weight (600 and 4000 g mol −1 ) and choliniumbased ionic liquids and salts containing anions derived from carboxylic acids (oxalate, malonate, succinate, L-malate, fumarate, glutarate and citrate), available in natural compounds, are here presented. Contrary to common ionic liquids, the cholinium-based ionic liquids used in this work are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 41 publications
1
48
0
Order By: Relevance
“…However, imidazolium‐based ILs display some toxicity and may compromise the biological activity of several molecules, thus motivating the research on more benign ILs to be applied in ABS. Albeit some reports have appeared in the past few years with this issue in mind, these studies were mainly carried out with cholinium‐based ILs, either combined with salts or with polymers to create ABS . Nevertheless, nowadays, there are other ILs derived from natural sources and that could be explored in the creation of ABS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, imidazolium‐based ILs display some toxicity and may compromise the biological activity of several molecules, thus motivating the research on more benign ILs to be applied in ABS. Albeit some reports have appeared in the past few years with this issue in mind, these studies were mainly carried out with cholinium‐based ILs, either combined with salts or with polymers to create ABS . Nevertheless, nowadays, there are other ILs derived from natural sources and that could be explored in the creation of ABS.…”
Section: Introductionmentioning
confidence: 99%
“…Albeit some reports have appeared in the past few years with this issue in mind, these studies were mainly carried out with cholinium-based ILs, either combined with salts or with polymers to create ABS. [19][20][21][22][23][24][25] Nevertheless, nowadays, there are other ILs derived from natural sources and that could be explored in the creation of ABS. Among these, analogues of glycine-betaine (AGB) can be seen as a promising alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al [3] studied theoretically the reaction of 1-butyl-3-methylimidazolium cation ([bmim] + ) with α-and β-glucose in presence and absence of triethylamine (base). Besides, the use of ILs as dissolution and derivatization media, imidazolium based ILs have also been proposed [28,29] to be an effective compound for the formation of aqueous biphasic systems (ABS).…”
Section: Introductionmentioning
confidence: 99%
“…Only a minimal discrepancy between the values from literature and our results was found. For example, we found a glass transition temperature for choline malonate ([Ch][Mal]) of −67 °C, while Mourão, et al reported −65 °C [31].…”
Section: Introductionmentioning
confidence: 91%
“…[Ch][Mal]) of −67 °C, while Mourão, et al reported −65 °C[31].Decomposition temperatures were measured to evaluate the thermal stability of the ILs. The Thermogravimetric Analysis (TGA) results for 5% mass decomposition in nitrogen and synthetic air obtained with a heating rate of 10 °C·min −1 are presented inTable 1.…”
mentioning
confidence: 99%